Money, Gender, and Power in Households: Conceptual Approaches - Ibragimova, Dilyara (Journal of Economic Sociology, 2016)
The bulk of the literature on processes related to the triad of money–power–inequality highlight power as the main driver. Given the causal relations, this view can be considered logical and reasonable. If research into these processes deals with the family (household) as an actor, the research appears to be enriched (more complex). As households often consist of men and women, biological sex and culturally constructed gender should be taken into account. Most researchers focusing on gender issues agree that gender relationships imply power relations. What is peculiar about family power relations and how are they related to money management? This article aims to depict the main perspectives related to the conceptualization of the indicated notions as well as, in part, their empirical operationalization. The first part of this article reviews power patterns developed by Steven Lukes, Michel Foucault, and Pierre Bourdieu and discusses issues related to definitions of “financial power” and its operationalization when applied to family relationships. The second part deals with economic and sociological concepts that reveal and explain the determinants of power relationships. The third part analyzes ongoing changes in the gender order and their potential effects on the structure of power functions in the family.